2002
DOI: 10.1590/s0100-41582002000400015
|View full text |Cite
|
Sign up to set email alerts
|

Variability in isolates of Puccinia polysora in Brazil

Abstract: The main objective of this work was to evaluate the variability of the southern rust pathogen Puccinia polysora in Brazil, based on its virulence on a set of maize (Zea mays) cultivars. Sixty single pustule isolates, from different areas of occurrence of southern rust, were evaluated for their virulence to 50 maize experimental hybrids. Six cultivars showed a clear distinction between susceptible and resistant reaction, and were used to characterize the variability of the pathogen. Seventeen virulence patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Although the race-specific genes are more practical to work in breeding programs and usually confer a significant level of resistance, the horizontal resistance commonly is more durable and provides protection against greater range of races. Therefore, in tropical areas as Brazil, considering the high incidence and severity of southern rust, the horizontal resistance should be considered as a long-term strategy (Casela and Ferreira 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although the race-specific genes are more practical to work in breeding programs and usually confer a significant level of resistance, the horizontal resistance commonly is more durable and provides protection against greater range of races. Therefore, in tropical areas as Brazil, considering the high incidence and severity of southern rust, the horizontal resistance should be considered as a long-term strategy (Casela and Ferreira 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Southern rust has become one of the main diseases affecting corn crops in Brazil, mainly those subjected to high temperature and humidity conditions (Ramirez-Cabral et al 2017;Casela and Ferreira 2002). Some factors such as the use of susceptible hybrids and monocropping in no-till systems in association with weather conditions favorable to inoculant outspread have increased the occurrence of this disease in Brazilian crops (Colombo et al 2014;Costa et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these fungal diseases are highly likely to occur as the models display. Common and southern rust CLIMEX models show large areas with optimal suitability for Africa and Latin‐America under current climate conditions; previous studies have shown that plant diseases are more frequent in these regions due to the tropical climate (Casela & Ferreira, ; Oerke, ). Moreover, southern rust is tropical and subtropical in distribution.…”
Section: Discussionmentioning
confidence: 97%